2014
DOI: 10.1002/1944-2866.poi377
|View full text |Cite
|
Sign up to set email alerts
|

Governments and Citizens Getting to Know Each Other? Open, Closed, and Big Data in Public Management Reform

Abstract: Citizens and governments live increasingly digital lives, leaving trails of digital data that have the potential to support unprecedented levels of mutual government–citizen understanding, and in turn, vast improvements to public policies and services. Open data and open government initiatives promise to “open up” government operations to citizens. New forms of “big data” analysis can be used by government itself to understand citizens' behavior and reveal the strengths and weaknesses of policy and service del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 23 publications
1
105
0
3
Order By: Relevance
“…Few projects speak to both stakeholders and citizens: researchers more commonly seek the perspective of either government employees (Clarke & Margetts, 2014;Mergel, 2014;Shackleton, Fisher, & Dawson, 2004) or citizens (e.g., Daou, Karuranga, Thiam, Mellouli, & Poulin, 2012;Kumar, Ureel, King, & Wallace, 2013). In a case study of the Singapore tax authority, Tan, Pan, and Lim (2005) identified stakeholders and their interests , but only spoke to government employees, relying on work from the early 1990s to provide taxpayer perspectives, thus leaving a gap in the literature for the exploration of the concerns of both stakeholders and citizens in an increasingly digitally mediated society.…”
Section: Challenges and Opportunities Of Connecting With Citizensmentioning
confidence: 99%
“…Few projects speak to both stakeholders and citizens: researchers more commonly seek the perspective of either government employees (Clarke & Margetts, 2014;Mergel, 2014;Shackleton, Fisher, & Dawson, 2004) or citizens (e.g., Daou, Karuranga, Thiam, Mellouli, & Poulin, 2012;Kumar, Ureel, King, & Wallace, 2013). In a case study of the Singapore tax authority, Tan, Pan, and Lim (2005) identified stakeholders and their interests , but only spoke to government employees, relying on work from the early 1990s to provide taxpayer perspectives, thus leaving a gap in the literature for the exploration of the concerns of both stakeholders and citizens in an increasingly digitally mediated society.…”
Section: Challenges and Opportunities Of Connecting With Citizensmentioning
confidence: 99%
“…The potential for real‐time, anywhere government‐to‐citizen communication has also raised interest in behavioral economics—more specifically, “nudge” (Behavioural Insights Team ; Charney ; Thaler ) approaches to social problem solving—and for gamification (King et al ; McCall, Koenig, and Kracheel ). Here, socially desirable citizen behaviour is incentivized through information cues, reducing the need for direct state intervention via “carrots and sticks.” In addition to these “information pushes,” governments are also turning to the social web for “information pulls,” collecting big data—large‐scale, unmediated and unstructured data—describing citizen behavior and preferences, as reflected in their interactions online, in order to inform more evidence‐based and/or democratically responsive policy development processes and service delivery improvements (Clarke and Margetts ; Keen et al ; Manyika et al ; Rutter ).…”
Section: Characteristics Of Digital Era Policy Design: An Instrumentsmentioning
confidence: 99%
“…In this study we are focusing on the use of open data in choosing between and evaluating decisions on allocating public resources (Clarke and Margetts, 2014). Data sets underpin any form of analysis or evaluation of policy options (or for that matter, post-implementation evaluation, which will use similar techniques) and their use has grown in parallel with the technical capability to process them (Lampathaki et al, 2010).…”
Section: Role Of Open Data In the Policy Contextmentioning
confidence: 99%